Dinamika Buzzer Politik terhadap Demokrasi dan Hak Asasi Manusia dalam Pemilu: Penelitian - Zayyin Abdul Quddus; Gustiana Sabarina (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The implementation of elections in Indonesia has brought about the phenomenon of political buzzers as an important aspect of political dynamics in the digital era. In the context of elections, the role of political buzzers has become increasingly significant in influencing public opinion, but also raises ethical issues and negative impacts on democracy and human rights. A qualitative research method was used to describe the role of political buzzers in elections, as well as their impact on democracy and human rights. The study results show that political buzzers can threaten democratic principles by spreading inaccurate information, manipulating public opinion, and creating a non-conducive political environment. Additionally, the negative impact of political buzzers also includes threats to human rights values, especially freedom of expression and the security of individuals in exercising their rights. To address these negative impacts, efforts are needed to closely monitor and regulate the practices of political buzzers, as well as to increase digital literacy among the public to better discern information received from social media. Thus, these efforts are expected to maintain the integrity of elections, ensure a healthy democratic process, and protect human rights values for all Indonesians.